Changes in Rubisco kinetics during the evolution of C4 photosynthesis in Flaveria (Asteraceae) are associated with positive selection on genes encoding the enzyme. - Kapralov, M; Kubien, D; Andersson, I; Filatov, D (2011)
Rubisco, the primary photosynthetic carboxylase, evolved 3-4 billion years ago in an anaerobic, high CO(2) atmosphere. The combined effect of low CO(2) and high O(2) levels in the modern atmosphere, and the inability of Rubisco to distinguish completely between CO(2) and O(2), leads to the occurrence of an oxygenation reaction that reduces the efficiency of photosynthesis. Among land plants, C(4) photosynthesis largely solves this problem by facilitating a high CO(2)/O(2) ratio at the site of Rubisco that resembles the atmosphere in which the ancestral enzyme evolved. The prediction that such conditions favor Rubiscos with higher kcat(CO2) and lower CO(2)/O(2) specificity (S(C/O)) is well supported, but the structural basis for the differences between C(3) and C(4) Rubiscos is not clear. Flaveria (Asteraceae) includes C(3), C(3)-C(4) intermediate, and C(4) species with kinetically distinct Rubiscos, providing a powerful system in which to study the biochemical transition of Rubisco during the evolution from C(3) to C(4) photosynthesis. We analyzed the molecular evolution of chloroplast rbcL and nuclear rbcS genes encoding the large subunit (LSu) and small subunit (SSu) of Rubisco from 15 Flaveria species. We demonstrate positive selection on both subunits, although selection is much stronger on the LSu. In Flaveria, two positively selected LSu amino acid substitutions, M309I and D149A, distinguish C(4) Rubiscos from the ancestral C(3) species and statistically account for much of the kinetic difference between the two groups. However, although Flaveria lacks a characteristic "C(4)" SSu, our data suggest that specific residue substitutions in the SSu are correlated with the kinetic properties of Rubisco in this genus.